2007
DOI: 10.1158/0008-5472.can-07-2415
|View full text |Cite
|
Sign up to set email alerts
|

CDC25B Involvement in the Centrosome Duplication Cycle and in Microtubule Nucleation

Abstract: Centrosome amplification is frequently reported in human cancers, although the molecular mechanisms that are responsible for this remain unclear. There is significant evidence to support a role for cyclin-dependent kinase (CDK)-cyclin complexes in centrosome duplication. The activities of CDKcyclin complexes are, in turn, regulated by the CDC25 family of phosphatases in a strict spatiotemporal manner, and we have recently reported that CDC25B localizes to the centrosomes from early S phase. In the present stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 45 publications
7
59
0
Order By: Relevance
“…[10][11][12][13] We have also recently demonstrated that overexpression of the CDC25B phosphatase causes centrosome overduplication, while overexpression of a catalytically inactive form has no effect on centrosome duplication. 14 In the present study, we report that CDC25B, along with other key cell cycle regulators, localise asymmetrically around the mother centrosome throughout interphase, and demonstrate a requirement for CDC25B in the normal centriole duplication cycle.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…[10][11][12][13] We have also recently demonstrated that overexpression of the CDC25B phosphatase causes centrosome overduplication, while overexpression of a catalytically inactive form has no effect on centrosome duplication. 14 In the present study, we report that CDC25B, along with other key cell cycle regulators, localise asymmetrically around the mother centrosome throughout interphase, and demonstrate a requirement for CDC25B in the normal centriole duplication cycle.…”
Section: Introductionsupporting
confidence: 54%
“…The observation that CDC25B localises to the mother centriole (Fig. 3B), which provides a platform for daughter centriole assembly, 28 and our recent evidence for CDC25B's involvement in centrosome overduplication, 14 suggested that CDC25B may also be involved in regulating early centrosome cycle events. We therefore studied the consequences of CDC25B loss of function on centriole duplication.…”
Section: Reportmentioning
confidence: 78%
See 1 more Smart Citation
“…Immunofluorescence studies were performed as previously described (26). Cellular DNA was counterstained with 4′,6-diamidino-2-phenylindole.…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9] At the G2/M transition, a pool of CDC25B is phosphorylated and activated by Aurora-A kinase at centrosomes, 10 where the initial activation of CDK1/Cyclin B complexes takes place, 11 suggesting that CDC25B might locally participate in the control of the onset of mitosis. Furthermore, CDC25B also participates in the control of g-Tubulin localization to the centrosomes, is involved in the centrosome duplication cycle, 12 and regulates proteasome-mediated degradation of centrin 2. 13 Centrosomes are the major microtubule organizing centers.…”
Section: Introductionmentioning
confidence: 99%